2015 54th IEEE Conference on Decision and Control (CDC) 2015
DOI: 10.1109/cdc.2015.7403431
|View full text |Cite
|
Sign up to set email alerts
|

Approximate regulation for nonlinear systems in presence of periodic disturbances

Abstract: In this work we present a new approach to the problem of output regulation for nonlinear systems in presence of periodic disturbances, possibly with an infinite number of harmonics. We show that, by adding a linear internal model, approximate regulation is achieved if the disturbance is small enough. Nominally all the harmonic included in the internal model are absent in the periodic steady state regulation error. Furthermore we show that the regulation error can be made arbitrarily small (in the L2 sense) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

7
0

Authors

Journals

citations
Cited by 16 publications
(53 citation statements)
references
References 16 publications
3
50
0
Order By: Relevance
“…Consistently, our main result aims to relate the performances on the regulation side with the performances of the corresponding identified model, expressed in terms of prediction error. Asymptotic regulation, in turn, will follow only when a right model exists that is in the "range" of the identifier used (and in this sense we observe how this design philosophy matches with the results of [23]).…”
Section: E Contribution Of the Paper And Notationsupporting
confidence: 61%
See 2 more Smart Citations
“…Consistently, our main result aims to relate the performances on the regulation side with the performances of the corresponding identified model, expressed in terms of prediction error. Asymptotic regulation, in turn, will follow only when a right model exists that is in the "range" of the identifier used (and in this sense we observe how this design philosophy matches with the results of [23]).…”
Section: E Contribution Of the Paper And Notationsupporting
confidence: 61%
“…The internal model is thus fixed a priori as an integrator acting on the error and the cascade is then stabilised using forwarding techniques. In [23] (see also [24,25]) this approach is extended to the case in which w is periodic, with a design that, however, guarantees only approximate regulation. In that works the internal model is fixed a priori as a linear system containing some of the harmonics of w(t), and a local state feedback stabiliser is used to force a periodic steady state, with the remarkable feature that the Fourier components of the steady state error associated to the harmonics contained in the internal model are zero.…”
Section: Early Approaches Avoiding the Chicken-egg Dilemmamentioning
confidence: 99%
See 1 more Smart Citation
“…The limits of the P P P 0 -robustness of the linear regulator motivate seeking for a regulation objective P P P for which a regulator that is P P P-robust relatively to more general topological spaces (F, τ F ) more likely could be constructed. As proposed in [23], in this section we let F = C 1 (X × U), τ F = τ C 1 and we consider a regulator of the kind (9) with (φ, θ) possibly nonlinear and with n im = (2d + 1)p e , for some arbitrary d ∈ N. We then choose a basis for R n × R nη in which (Φ, G) read as…”
Section: B Robustness In the P P P T Sensementioning
confidence: 99%
“…Nevertheless, no conceptual progress has been made in terms of extensions to larger classes of systems compared to their pre-processing counterparts. A different approach to the design of post-processing regulators was recently pursued by Astolfi, Praly and Marconi 22,23 , where the linear regulator is attached to a class of nonlinear systems. In particular, the authors have shown that the output regulation problem can be solved robustly 24 by a post-processing integral action whenever the steady state is made of equilibria 23 , and then Astolfi, Praly and Marconi 22 have extended the results to the case in which the steady-state signals are periodic, obtaining, however, only an approximate result stating that the Fourier coefficients in the regulation errors corresponding to the frequencies embedded in the internal model vanish at the steady state.…”
Section: Introductionmentioning
confidence: 99%